Beneficial Effect of Thymelaea hirsuta on Pancreatic Islet Degeneration, Renal Fibrosis, and Liver Damages as Demonstrated in Streptozotocin-Induced Diabetic Rat - Abid, Sanae (ScientificWorldJournal, 2021)
OBJECTIVE: In Morocco, Thymelaea hirsuta (T. hirsuta) (Thymelaeacea) is a medicinal plant widely used to treat and prevent diabetes. The present study aimed to evaluate the medium-term antidiabetic effect of aqueous extract (AqTh) and ethyl acetate fraction (EaTh) of Th and to investigate their putative protective effect on pancreatic islet degeneration, diabetic nephropathy, and liver damages in streptozotocin (STZ)-diabetic rats. METHODS: Experimental diabetes in rats was induced by a single intraperitoneal injection of 50 mg/kg of STZ. During the treatment period (4 weeks), 200 mg/kg AqTh and 50 mg/kg EaTh were orally administrated daily to STZ-diabetic rats. A group of parameters including fasting blood glucose, biochemical parameters, and intestinal α-glucosidase inhibition were studied. Furthermore, histological study of the pancreas, kidney, liver, and aorta was also realized. RESULTS: At the end of the treatment, both AqTh and EaTh had normalized fasting blood glucose to 1.08 and 1.25 g/l, respectively. AqTh has also reduced urinary creatinine and HbAc1. The EaTh showed inhibitory activity against intestinal α-glucosidase, whereas AqTh did not have this inhibitory effect. Furthermore, pancreas hematoxylin and eosin staining showed that AqTh or EaTh prevents pancreatic islet cell degeneration. As the same kidney, Masson's trichrome staining has shown a significant prevention of renal fibrosis in AqTh- or EaTh-treated diabetic rats. On the other hand, liver hematoxylin and eosin staining showed that AqTh and EaTh prevent liver damage. CONCLUSION: We conclude that medium-term administration of AqTh and EaTh exerts significant antihyperglycemic effect in STZ-diabetic rats possibly through intestinal α-glucosidase inhibition and protection against pancreatic islet cell damage. Moreover, AqTh and EaTh treatment prevent nephropathy and liver complications in STZ-diabetic rats.